The precise measurement of car velocity - Barzdžiukas, Julius; Augutis, Stasys V.; Žilinskas, Rimvydas P. (Transport, 2012)
The system for precise measurement of car velocity is using lasers and reference distance fixed on the car. Primary application for this system is verification and calibration of stationary velocity meters without the need for disassembling or transporting them to testing area. Velocity measurements can be performed under the real traffic conditions. Principle of operation, calibration of the measurement system and uncertainties are provided. Some solutions used in this system operate in a wide range of possible environmental conditions. Additionally, ABS sensors were used for dynamic car velocity evaluation. Possibilities of this system, when used in combination with optical measurements, are provided. Experimental data demonstrates ABS sensor applicability in measurements with different road types, tire pressures and temperatures.First Published Online: 26 Jun 2012